Discontinuation and switching patterns of tumour necrosis factor inhibitors (TNFis) in TNFi-naive and TNFi-experienced patients with psoriatic arthritis: an observational study from the US-based Corrona registry - Philip J Mease; Jeffrey D Greenberg; Chitra Karki; Mei Liu; YouFu Li; Bernice Gershenson; Hua Feng; Peter Hur (RMD Open)
Objective To examine patterns of tumour necrosis factor inhibitor (TNFi) use in TNFi-naive and TNFi-experienced patients with psoriatic arthritis (PsA) in the USA.Methods All patients aged ≥18 years with PsA enrolled in the Corrona Psoriatic Arthritis/Spondyloarthritis Registry who initiated a TNFi (index therapy) between March 2013 and January 2017 and had ≥1 follow-up visit were included. Times to and rates of discontinuation/switch of the index TNFi were compared between TNFi-naive and TNFi-experienced cohorts. Patient demographics and disease characteristics at the time of TNFi initiation (baseline) were compared between cohorts and between patients who continued versus discontinued their index TNFi by the first follow-up visit within each cohort.Results This study included 171 TNFi-naive and 147 TNFi-experienced patients (total follow-up, 579.2 person-years). Overall, 75 of 171 TNFi-naive (43.9%) and 80 of 147 TNFi-experienced (54.4%) patients discontinued their index TNFi; 33 of 171 (19.3%) and 48 of 147 (32.7%), respectively, switched to a new biologic. TNFi-experienced patients had a shorter time to discontinuation (median, 20 vs 27 months) and were more likely to discontinue (p=0.03) or switch (p<0.01) compared with TNFi-naive patients. Among those who discontinued, 49 of 75 TNFi-naive (65.3%) and 59 of 80 TNFi-experienced (73.8%) patients discontinued by the first follow-up visit; such patients showed a trend towards higher baseline disease activity compared with those who continued.Conclusions The results of this real-world study can help inform treatment decisions when selecting later lines of therapy for patients with PsA.